Louisburg Square, ca. 1870-1900 - Unknown (Tufts Archival Research Center, 2005)
Street-level view southwest of Louisburg Square, located between Pinckney Street to the north-northwest and Mt. Vernon Street to the south-southeast. Houses lining the west side of Louisburg Square are included in the right-half of the photograph. Houses lining the south-southeast side of Mt. Vernon Street are included in the left-half of the photograph. Two small children stand beside a wrought-iron fence that encircles the park located in the center of the square. A horse-drawn carriage is visible along the east side of Louisburg Square. A street-lamp is visible on the north-northeast corner of Pinckney Street and Louisburg Square. Copyprint 4 5/8 x 7 3/8, 4 7/8 x 7 11/16 overall Photographs